The Relationship Between Poverty Levels Among Men and Women and the Indonesian Economy - Shafira Niken Sari; Endang Endang; Devi Aria Nanda; Istikomah Istikomah (Universitas Bina Sarana Informatika, 2025)
The global economy increasingly emphasizes development in terms of the economy that must be able to improve people's standard of living to achieve progress. Labor force participation is one of the important factors influencing economic growth, where the role of women in the workforce is often hampered by gender inequality that still exists in Indonesia. This study aims to analyze the relationship between the level of male and female participation in the workforce to the Indonesian economy. This study uses secondary data from the Central Statistics Agency (BPS) to analyze the differences in labor participation between men and women, and their impact on macroeconomic indicators. Using the panel data regression analysis method, this study compares the effect of male and female labor force participation on economic growth in various provinces in Indonesia. The results of the study show that there is an effect on male LFPR and female LFPR, although male participation in the workforce is higher than women, increasing female participation can make a significant contribution to the Indonesian economy, especially in sectors that require skilled workers. This study can help the Indonesian government in making the right policies.